Dietary patterns and social deficiencies put preschoolers in rural areas at risk of malnutrition. - Calderón-Martínez, María Elena; Taboada-Gaytán, Oswaldo Rey (Agricultura, Sociedad y Desarrollo, 2024)
Infant malnutrition is an ongoing multi-causal problem with serious consequences for individual and public health worldwide. Preschool children in rural areas represent the most vulnerable group; however, there is no research focused on micro-regions to provide accurate information about their nutritional status and underlying causes. The objective of this study was to determine the prevalence of infant malnutrition in Tochimilco, Puebla, and to specify the factors that influence nutritional status, both internal and external. A nutritional evaluation based on anthropometry and clinical and dietary history was carried out on 61 preschoolers; a semi-structured questionnaire was applied to 38 children from this population to analyze social and environmental variables that referred to descriptive and multivariate statistics. It was found that 51% are at risk of malnutrition, 48% manifest height/age deficit and 35% are underweight. Furthermore, the type of rural/urban locality influenced nutritional status; government support also related to weight/height and weight/age, with particular reference to the scholarship program. Eating patterns provide sufficient energy and macronutrients, but of very poor quality. In conclusion, the infant population of Tochimilco is at greater risk of malnutrition than reported and the most efficient strategy to eradicate this is not only to improve living conditions and social deficiencies, but to include the component of nutritional education.